Education recovery model in Takaful education plan and its acceptance level among special education teachers - Nur Arifah Amran (2017)
According to statistics, the number of learning disabled children is on the increase. The current cost for higher education is also expensive. Usually the parents of the normal children can have better financing and get many benefits by participating in the takaful education plan. However, the learning disabled children cannot get the same benefits as the existing models of takaful do not provide special plan for them. The learning disabled children can achieve a better condition with a consistent guidance hence something must be done to help them or else it may become a burden for the country, parents and special ducation teachers. Thus they need a special plan of takaful in recovery. The first objective of this study is to compare the existing takaful education plan for the teaching support of the learning disabled children. The second objective is to construct new education recovery model in takaful education plan. The third objective is to identify the level of acceptance towards the model constructed among special education teachers. Firstly a comparison of needed information from takaful product brochures are made and studied. Then a new education recovery model of education plan in teaching support is constructed based on the integrated model of takaful. This education recovery model consists plan which assists the special education teachers in educating the learning disabled children. A sample of 260 school teachers of special education in Terengganu state is questioned using designated questionnaire to find their acceptance on the proposed model. The result is analyzed using SPSS (non-parametric) in order to determine the significant acceptance for this plan. Four life tables oftakaful education plan was successfully constructed. The findings showed that by using Spearman's Correlation, the independent variables (reading disability, writing disability, calculating disability and the need of teaching support) had positive and significant correlation with dependent variable (acceptance of special education teachers on the new takaful education plan) which indicates the acceptance towards the plan. The takaful education plan special for the learning disabled children may help the process of recovery of the learning disabled children. Besides that, it help the parents in managing finance for their children's higher education and reduce the burden of the special education teachers.